Avifauna of the specially protected natural areas Chelyabinsk (city) and Kashtak forests (Chelyabinsk Oblast) and problems of their protection - Gashek V.A.; Krasutskiy B.V. (Ecosystem Transformation, 2024)
Based on original data obtained in 2017–2022 on the territory of two specially protected natural areas of regional significance, as well as literary sources and information from respondents, faunistic lists of birds were compiled, dominants and subdominants were identified. In the Chelyabinsk (City) Forest with adjacent territories 151 species were recorded from 1987 to 2022, of which 74 are reliably assumed to be nesting. In 2017–2022 the dominants in the nesting period were Chaffinch and the Wood Warbler, the group of subdominants was made up of the Great Tit, the Willow Tit and the European Pied Flycatcher. Transformation of the ecosystem of the Chelyabinsk forest from the 1980s to the 2010s led to the disappearance of Black Grouse, Eurasian Nightjar, Golden Eagle, Redfooted Falcon, and in adjacent territories – Common Moorhen, Eurasian Oystercatcher, Grey Partridge, Common Quail, Short-eared Owl. Under the influence of recreational activities, there was a reduction in the number and abundance of ground-nesting species: the Yellowhammer has disappeared; the Tree Pipit is not numerous and comprises up only 2% of the total bird population. A number of nesting species (Northern Goshawk, Ural Owl, Eurasian Bullfinch, Chaffinch) showed ethological adaptations indicating synurbization. In the less anthropogenically disturbed Kashtak Forest for the period 2018–2022 more breeding and presumably nesting species were found (81), including urbophobic species (Common Buzzard, Black Grouse, Western Capercaillie); the total list of birds was 101 species. During the nesting period, the Chaffinch, the Wood Warbler and the Tree Pipit dominated, the group of subdominants included the Great Tit, the European Pied Flycatcher and the Common Redstart.